2020
DOI: 10.11648/j.ijtet.20200602.11
|View full text |Cite
|
Sign up to set email alerts
|

A Disaster Resilient Road: Effects of Fines on Density and Shear Strength of Sands

Abstract: During a massive flood or earthquake, the roads are mainly damaged due to the looseness of the subgrades. In recent times for any new constructions of roads and embankments the subgrades mainly constructed with the sand filling. It is difficult to achieve the desired degree of compaction beyond a certain limit. That's why the bases (subgrades) become loose. This study aims to overcome the situation by increasing compaction and shear strength properties of sand filling. In this paper, an intensive laboratory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Very few results are available in the literature on direct shear tests performed on reconstituted sand-clay mixtures in the laboratory [39,42,50,60,73,175,176]. Furthermore, the results do not provide a comprehensive understanding on the mechanical behavior of the sand-clay mixtures even though they clearly indicate that the clay content affects the shear behavior of the mixtures.…”
Section: Interface Direct Shear Tests On Sand-clay Mixturementioning
confidence: 98%
“…Very few results are available in the literature on direct shear tests performed on reconstituted sand-clay mixtures in the laboratory [39,42,50,60,73,175,176]. Furthermore, the results do not provide a comprehensive understanding on the mechanical behavior of the sand-clay mixtures even though they clearly indicate that the clay content affects the shear behavior of the mixtures.…”
Section: Interface Direct Shear Tests On Sand-clay Mixturementioning
confidence: 98%
“…For a fine content greater than 60 percent, the shear strength of the mixtures is equivalent to that of pure clay [41]. In these cases (i.e., fine content > 60%), the decrease in fine content (i.e., the increase in sand-size particle fraction) results in an increase in the internal friction angle [42,43]. Tsubakihara et al [44] reported similar effects of particle size on the shear strength of the soil-steel interface.…”
Section: Effects Of Cement Content On Shear Strength and Interface Sh...mentioning
confidence: 99%